A Seeded Sample of Concealed-Carry Permit Holders - Smith, Tom W. (Journal of quantitative criminology, 2003)
A pilot study using a seeded sample finds that gun-carrying and permit holding are accurately reported by concealed-carry permit holders. This is consistent with the findings of past validation studies of gun ownership. Moreover, the similarity in gun uses across the seeded and cross-section samples indicates that both collect consistent data.